Effect of Vitamin A on Lung Function Test in patient with Chronic Bronchial Asthma (TAJ: Journal of Teachers Association, 2018)
In chronic bronchial asthma inflammation may be accompanied by intensive air flow limitation. Endogenous oxidants produced by overactive inflammatory cells destroy airway epithelium which slough into bronchial lumen and thus aggravates asthma. When oxidant overwhelm anti-oxidants, tissue injury and disease results. It is observed that decrease level of anti-oxidants in the lungs is a feature of chronic bronchial asthma and that there is a marked decrease of these levels during acute asthmatic attacks. These observations highlight the positive correlation between anti-oxidant therapy in asthmatic patients. The study was carried out to observe the changes in lung function in patients with chronic bronchial asthma both before and after supplementation of anti-oxidant vitamin A. Pulmonary function variables such as FVE, FEV1, FEV1/FVC%and PEFR were measured by spirometer in patients with chronic bronchial asthma both before and three month after supplementation of vitamin A 10,000 I.U orally daily. The mean FVC, FEV1, FEV1/FVC% and PEFR following vitamin A was unchanged significantly (P